Role of RacC for the Regulation of WASP and Phosphatidylinositol 3-Kinase during Chemotaxis of Dictyostelium - Han, Ji W. (2006)
WASP family proteins are key players for connecting multiple signaling pathways to F-actin polymerization. To dissect the highly integrated signaling pathways controlling WASP activity, we identified a Rac protein that binds to the GTPase binding domain of WASP. Using two-hybrid and FRET-based functional assays, we identified RacC as a major regulator of WASP. RacC stimulates F-actin assembly in cell-free systems in a WASP-dependent manner. A FRET-based microscopy approach showed local activation of RacC at the leading edge of chemotaxing cells. Cells overexpressing RacC exhibit a significant increase in the level of F-actin polymerization upon cAMP stimulation, which can be blocked by a phosphatidylinositol (PI) 3-kinase inhibitor. Membrane translocation of PI 3-kinase and PI 3,4,5-trisphosphate reporter is absent in racC null cells. Cells overexpressing dominant negative RacC mutants and racC null cells move at a significantly slower speed and show a poor directionality during chemotaxis. Our results suggest that RacC plays an important role in PI 3-kinase activation and WASP activation for dynamic regulation of F-actin assembly during Dictyostelium chemotaxis.